Screening Anionic Groups Within Zwitterionic Additives for Eliminating Hydrogen Evolution and Dendrites in Aqueous Zinc Ion Batteries - Wang, Biao; Guan, Chaohong; Zhou, Qing; Wang, Yiqing; Zhu, Yutong; Bian, Haifeng; Chen, Zhou; Zhang, Shuangbin; Tan, Xiao; Luo, Bin; Tang, Shaochun; Meng, Xiangkang; et al. (Nano-Micro Letters, 2025)
Zwitterionic materials with covalently tethered cations and anions have great potential as electrolyte additives for aqueous Zn-ion batteries (AZIBs) owing to their appealing intrinsic characteristics and merits. However, the impact of cationic and anionic moieties within zwitterions on enhancing the performance of AZIBs remains poorly understood. Herein, three zwitterions, namely carboxybetaine methacrylate (CBMA), sulfobetaine methacrylate (SBMA), and 2-methacryloyloxyethyl phosphorylcholine (MPC), were selected as additives to investigate their different action mechanisms in AZIBs. All three zwitterions have the same quaternary ammonium as the positively charged group, but having different negatively charged segments, i.e., carboxylate, sulfonate, and phosphate for CBMA, SBMA, and MPC, respectively. By systematical electrochemical analysis, these zwitterions all contribute to enhanced cycling life of Zn anode, with MPC having the most pronounced effect, which can be attributed to the synergistic effect of positively quaternary ammonium group and unique negatively phosphate groups. As a result, the Zn//Zn cell with MPC as additive in ZnSO4 electrolyte exhibits an ultralong lifespan over 5000 h. This work proposes new insights to the future development of multifunctional zwitterionic additives for remarkably stable AZIBs. Highlights: 1 Three zwitterions with identical quaternary ammonium cations but distinct anionic groups, i.e. carboxylate, sulfonate and phosphate, show distinct impact in aqueous zinc ion batteries. 2 The zwitterion with phosphate group (2-methacryloyloxyethyl phosphorylcholine, MPC) uniquely promotes oriented Zn (002) plane deposition and provides pH buffering capability, effectively suppressing dendrite formation and side reactions. 3 The Zn//NaVO full cell with MPC additive delivers an ultralong cycling life of 4000 cycles with an exceptionally low capacity decay of 0.014% per cycle.